Peru : Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Peru's Request for a Stand-By Arrangement (SBA). Performance under the 2002-03 SBA was satisfactory. This performance provides a solid basis for continuing with policies aimed at maintaining macroeconomic stability. The authorities are requesting a 26-month SBA covering the period through August 2006, when a new administration is scheduled to take office. They consider that continued IMF support for their program would help anchor economic policymaking and improve investor sentiment. To boost economic growth and promote employment, the authorities are committed to implementing a broad set of structural reforms.